Legal Policy Pembatasan Hak Politik Anggota Kepolisian dan Prajurit TNI di Indonesia: Sebuah Evaluasi - Rahadian Diffaul Barraq Suwartono (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Political rights’ limitation for members of the police and TNI soldiers is an old issue that has almost been forgotten. However, this issue is back to become relevant when the 2024 General Elections are held. The spirit of regulating legal policies to limit political rights can be traced back to the embryonic formation of the TNI as a national armed force before Indonesia's independence. The Indonesian military, which was born with a unique character as a people's army, is positioned as a stabilizer of the political life of the nation and state through the conception of the Middle Way and the Dual Functions of ABRI. However, at the end of the New Order, this policy gave rise to excesses that harmed human rights and democracy in Indonesia. This article describes this problem in the form of a research formulation: what is the background to limiting the political rights of members of the National Police and TNI soldiers? And; Do these restrictions on political rights still need to be maintained? This is because efforts are starting to emerge to eliminate restrictions on political rights for TNI soldiers and members of the National Police. This article describes the grand design of the legal policy on these restrictions. This restriction is still relevant today and needs to be strengthened again after the 2024 elections. A thorough evaluation is required to ensure this legal policy can survive.